Defining a Flexible Notion of “Good” STEM Writing Across Contexts: Lessons Learned From a Cross-Institutional Conversation - Grady, Sara M.; Morton-Aiken, Jenna; Druschke, Caroline Gottschalk; Lofgren, Ingrid E.; Karraker, Nancy E.; McWilliams, Scott R.; Reynolds, Nedra; Finan, Elaine; Wolter, Patti L.; Leff, Donna R.; Kennedy, Michael (Frontiers in Communication, 2022)
We respond to a surging interest in science communication training for graduate scientists by advocating for a focus on rhetorically informed approaches to STEM writing and its assessment. We argue that STEM communication initiatives would benefit by shifting from a strategic focus on products to a flexible understanding of writing as a practice worthy of attention and study. To do that, we use our experience across two universities and two distinct programmatic contexts to train STEM graduate students in writing and communication. We draw from cross-disciplinary conversations to identify four facets of “good” STEM writing: 1) connecting to the big picture; 2) explaining science; 3) adhering to genre conventions; and 4) choosing context-appropriate language. We then describe our ongoing conversations across contexts to develop and implement flexible rubrics that capture and foster conversations around “good” writing. In doing so, we argue for a notion of writing rubrics as boundary objects, capable of fostering cross-disciplinary, integrative conversations and collaborations that strengthen student writing, shift STEM students towards a rhetorically informed sense of “good” writing, and offer that kinds of assessment data that make for persuasive evidence of the power of writing-centric approaches for STEM administrators and funders.